A review of evolving remote sensing and automated techniques in rock glacier mapping - Sunil Tamang; Shelley MacDonell; Benjamin Aubrey Robson; James Shulmeister; James Brasington (Earth-Science Reviews, 2026)

Changing antimicrobial prescribing patterns, and laboratory reporting in Enterococcus faecalis infective endocarditis at a tertiary Australian centre - Nilanthy Vigneswaran; Kyra Y. L. Chua; Sadid Khan; Tony M. Korman; Benjamin Rogers; Christopher Robson (European Journal of Clinical Microbiology & Infectious Diseases, 2026)

Contrasting Dynamic Behaviour of Five Lake-terminating Glaciers Draining the Vatnajökull Ice Cap and Links to Bedrock Topography - Nathaniel R. Baurley; Amelia Andrews; Benjamin Robson; Sherif Attia; Kirk Martinez; Jane K. Hart (Remote Sensing in Earth Systems Sciences, 2025)
Over recent years, the rapid growth and development of proglacial lakes at the margin of many of Iceland’s outlet glaciers has resulted in heightened rates of mass loss and terminus retreat, yet the key processes forcing their dynamic behaviour remain uncertain, particularly at those glaciers which are underlain by overdeepened bedrock troughs. As such, we utilised satellite remote sensing to investigate the recent dynamic changes at five lake-terminating glaciers draining the Vatnajökull ice cap. Specifically, we quantified variations in surface velocity between ~ 2008–2020, alongside datasets of frontal retreat, proglacial lake growth, bedrock topography and ice surface elevation change to better understand their recent dynamics and how this may evolve in future. We observed contrasting dynamic behaviour between the five study glaciers, with three displaying a heightened dynamic response (Breiðamerkurjökull, Fjallsjökull, Skaftafellsjökull), which was likely driven by retreat down a reverse-sloping bed into deeper water and the onset of dynamic thinning. Conversely, one glacier re-advanced (Kvíárjökull), whilst the other remained relatively stable (Svínafellsjökull), despite the presence of overdeepened bedrock troughs under both these glaciers, highlighting the complex nature of those processes that are driving the dynamic behaviour of lake-terminating glaciers in this region. These findings may be important in helping understand the processes driving the dynamics of other lake-terminating glaciers in Iceland so that their future patterns of retreat and mass loss can be more accurately quantified.

The Physical Home Food Environment in Relation to Children’s Diet Quality and Cardiometabolic Health - Adriana Verdezoto Alvarado; Kaelyn F. Burns; Benjamin Brewer; Shannon M. Robson (Journal of the Academy of Nutrition and Dietetics, 2025)

Stable isotope analyses of lacustrine chitinous invertebrate remains: Analytical advances, challenges and potential - Angela L. Lamb; Benjamin D. Barst; Clayton D. Elder; Stefan Engels; Chris Francis; Maarten van Hardenbroek; Oliver Heiri; Alex Lombino; Hannah J. Robson; Katey Walter Anthony; Matthew J. Wooller (Quaternary Science Reviews, 2024)

Investigation of the 2010 rock avalanche onto the regenerated glacier Brenndalsbreen, Norway - Siri H. Engen; Marthe Gjerde; Thomas Scheiber; Gernot Seier; Hallgeir Elvehøy; Jakob Abermann; Atle Nesje; Stefan Winkler; Kristine F. Haualand; Denise C. Rüther; Alexander Maschler; Benjamin A. Robson; et al. (Landslides, 2024)
Rock avalanches onto glaciers are rare in Norway. Here, we examine a rock avalanche that spread onto the regenerated Brenndalsbreen, an outlet glacier from Jostedalsbreen ice cap. The rock avalanche is intriguing in that limited information exists with respect to the exact time of failure, location of detachment area, and preparatory and triggering processes. Based on an analysis of ice stratigraphy and photographic documentation, we assess that the event happened between mid-March and June 4, 2010. A potential triggering factor could have been heavy snow and rainfall combined with above freezing air temperatures on March 18–19, 2010. We use digital terrain models to determine that the detachment area is at an almost vertical rock slope in a narrow gorge above Lower Brenndalsbreen. The deposit volume is estimated to 0.130 ± 0.065 Mm 3 , and the H / L ratio and fahrböschung are 0.45 and 24°, respectively. We apply a Voellmy flow model to confirm the detachment location and volume estimate by producing realistic runout lengths. Although glacial debuttressing may have been a likely preparatory process, the detachment area was exposed for 45–70 years before the rock avalanche occurred. The supraglacial rock avalanche debris was separated into two branches with a distinct melt-out line across the glacier. The debris reached the glacier front in 2019 and 2020, where it started being deposited proglacially while Lower Brenndalsbreen kept receding. The 2010 Brenndalsbreen rock avalanche may not be a unique event, as deposits constituting evidence of an old rock avalanche are currently melting out at the glacier front.

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

CropPol : A dynamic, open and global database on crop pollination - Alfonso Allen‐Perkins; Ainhoa Magrach; Matteo Dainese; Lucas A. Garibaldi; David Kleijn; Romina Rader; James R. Reilly; Rachael Winfree; Ola Lundin; Carley M. McGrady; Claire Brittain; David J. Biddinger; et al. (Ecology, 2022)
Seventy five percent of the world's food crops benefit from insect pollination. Hence, there has been increased interest in how global change drivers impact this critical ecosystem service. Because standardized data on crop pollination are rarely available, we are limited in our capacity to understand the variation in pollination benefits to crop yield, as well as to anticipate changes in this service, develop predictions, and inform management actions. Here, we present CropPol, a dynamic, open, and global database on crop pollination. It contains measurements recorded from 202 crop studies, covering 3,394 field observations, 2,552 yield measurements (i.e., berry mass, number of fruits, and fruit density [kg/ha], among others), and 47,752 insect records from 48 commercial crops distributed around the globe. CropPol comprises 32 of the 87 leading global crops and commodities that are pollinator dependent. Malus domestica is the most represented crop (32 studies), followed by Brassica napus (22 studies), Vaccinium corymbosum (13 studies), and Citrullus lanatus (12 studies). The most abundant pollinator guilds recorded are honey bees (34.22% counts), bumblebees (19.19%), flies other than Syrphidae and Bombyliidae (13.18%), other wild bees (13.13%), beetles (10.97%), Syrphidae (4.87%), and Bombyliidae (0.05%). Locations comprise 34 countries distributed among Europe (76 studies), North America (60), Latin America and the Caribbean (29), Asia (20), Oceania (10), and Africa (7). Sampling spans three decades and is concentrated on 2001–2005 (21 studies), 2006–2010 (40), 2011–2015 (88), and 2016–2020 (50). This is the most comprehensive open global data set on measurements of crop flower visitors, crop pollinators and pollination to date, and we encourage researchers to add more datasets to this database in the future. This data set is released for non‐commercial use only. Credits should be given to this paper (i.e., proper citation), and the products generated with this database should be shared under the same license terms (CC BY‐NC‐SA).

Predicting the seasonal evolution of southern African summer precipitation in the DePreSys3 prediction system - Paul-Arthur Monerie; Jon Robson; Buwen Dong; Bastien Dieppois; Benjamin Pohl; Nick Dunstone (Climate Dynamics, 2019)